The Relationship Between Referential and Grammatical Meaning in Arabic Nouns: A Structural-Semantic Perspective - Randi Safii; Rifki Alfatih; Cutri A. Tjalau; Dwi Marselina Mumu (Faculty of Education and Teacher Training, 2026)
This study, titled “The Relationship Between Referential Meaning and Grammatical Meaning in Arabic Nouns from a Structural-Semantic Perspective,” aims to uncover the relationship between lexical meaning that refers to reality (referential meaning) and meaning formed through syntactic structure (grammatical meaning) in the Arabic language, particularly in the use of nouns in classical literary texts. This study is grounded in structural semantics, which emphasizes the interconnection between linguistic elements in forming a cohesive system of meaning. The research method employed is a qualitative descriptive approach using content analysis. The research data were drawn from verses of the Mu‘allaqah by Imru’ al-Qais, which are rich in noun forms and variations in grammatical structure. Each noun (isim) was analyzed based on its referential context and its function within the sentence structure. The results indicate that the referential meaning of Arabic nouns—such as the words “حبيب,” “منزل,” and “الآرام”—is closely linked to their grammatical meaning, which governs the word’s position and function within the sentence context. The relationship between the two forms a complex network of meaning: referential meaning provides the conceptual foundation, while grammatical meaning clarifies the syntactic and emotional relationships within the text. Thus, the interaction between these two types of meaning enriches the semantic and aesthetic interpretation of classical Arabic poetry.